Investigation into the detonation performances of Urea Hydrogen Peroxide (UHP) - Halleux, Francis (Cranfield University, 2023)
Within the scope of countering the threat of Improvised Explosive Devices, Home Made Explosives constitute a major public security concern, requiring specific risk assessments for first responders such as Explosive Ordnance Disposal (EOD) teams. Among potential emerging threats, Urea Hydrogen Peroxide (UHP) is investigated, considering the ease of manufacture combined with the availability of its precursors. Previous research from the same authors demonstrated UHP detonability at small-scale under heavy confinement and provided an initial characterisation (lab-scale) of detonation performance parameters. As a maximum of experimental data is particularly desirable to accurately evaluate the detonation parameters of non-ideal explosives, initial lab characterisation is here completed and complemented by field and underwater instrumented firings using scaled-up charges.
Keywords: Detonation; Performance; Urea Hydrogen Peroxide; DSDS22 Poster; DSDS22